Melanocytic or Not? Dermoscopy and Reflectance Confocal Microscopy for Lesions Difficult to Diagnose: A Cross-Sectional Diagnostic Accuracy Study - Scharf, Camila; Argenziano, Giuseppe; Brancaccio, Gabriella; Licata, Gaetano; Ronchi, Andrea; Moscarella, Elvira (Dermatology Practical & Conceptual, 2021)
Background: Different techniques for non-invasive skin examination and early diagnosis of skin lesions are available nowadays, being dermoscopy and reflectance confocal microscopy (RCM) the most diffused ones. Several studies supported the complementary use of dermoscopy and RCM that improves diagnostic accuracy when dealing with melanocytic lesions.Objectives: To analyze RCM diagnostic accuracy in the differential diagnosis between melanocytic and non-melanocytic lesions.Methods: This is a cohort selected cross-sectional study conducted at the Dermatology Unit of the University of Campania L. Vanvitelli, Naples, Italy, from 2012 to 2020. We searched the image database for all excised lesions for which the clinical and dermatoscopic differential diagnosis was between melanocytic and non-melanocytic and for which an RCM examination was performed. Sensitivity, specificity, and diagnostic accuracy values ​​were estimated. Results: The study included 53 cases that were found to have disagreement between clinical, histological and RCM diagnosis, of which, in 31 cases the differential diagnosis was melanocytic vs non-melanocytic lesion. The RCM reached a specificity of 87% (95% CI: 0.73-1) and a sensitivity of 62.5% (95% CI: 0.29-0.96) in the present sample. Diagnostic accuracy was 80.6% (95% CI: 0.67-0.94).Conclusion: RCM has a high specificity in differentiating between difficult-to-diagnose melanocytic and non-melanocytic lesions.